Ambient air quality of Katra town, J&K during fireworks on Diwali festival - Anil K. Raina; Anita Sharma (Environment Conservation Journal, 2013)
Diwali-the festival of lights, is celebrated in India, every year during October or November with great fireworks display which contributes to pollution of air. In order to assess the impacts of fireworks on ambient air quality during Diwali festival in Katra town, Jammu , (J&K); monitoring of RSPM, NRSPM, SO2 and NO2 during day and night times for Pre-Diwali (day before Diwali); Diwali and Post-Diwali (day after Diwali) for two successive years i.e. 2011 and 2012 has been carried out in a residential area. The air quality levels observed on Diwali has been compared with the air quality levels observed before and after Diwali which has revealed considerable increase in RSPM, NRSPM, SO2 and NO2 concentration due to Diwali fireworks. On Diwali day, the concentration of  RSPM, NRSPM, TSPM, SO2 and NO2 was found to be 118.27µg/m³,  153.2µg/m³,  271.47µg/m3, 6.61µg/m3 and 10.51µg/m3 respectively in 2011 and 141.2µg/m³, 199.14µg/m³,  340.34µg/m³, 7.06µg/m³ and 10.53µg/m³ respectively in 2012.These concentrations were found to be 1.75,  1.57, 1.65, 1.73 and 1.52 times higher  in 2011 and 1.86, 2, 2, 1.47 and 1.39 times higher in  2012,  when compared with the respective concentrations of  normal day. The higher level of these pollutants due to fireworks during Diwali festival poses serious health hazards to the inhabitants of the area.